Experimental model for percutaneous tracheostomy training - Caroline Schmiele Namur; Kassem Samir Saleh; Marianne Yumi Nakai; Alexandre Baba Suehara; Antonio Jose Gonçalves (Brazilian Journal of Otorhinolaryngology)
Objective: To propose a practical and accessible model that enables the training of this technique. Methods: The model comprises a structure composed of a wood board resting on a PVC tube. A foam block on which the pig trachea is supported is placed on this structure. A foam sheet covered with fabric is placed over the trachea to simulate the soft parts of the neck and the skin. This is a practical training model for practice of surgeons in percutaneous tracheostomy. A questionnaire on the assessment of the proposed model to each participating surgeon was applied. Results: Ten surgeons underwent training on the model: two experienced head and neck surgeons, three specialty residents, one otorhinolaryngologist, and three general surgery residents. All of them were able to perform the procedure successfully. Conclusion: The proposed simulation model presented good results when applied to surgeons, and it is a possible alternative to percutaneous tracheostomy training. Level of evidence: Level III.